FRI0330 Rituximab therapy in sle: early retreatment is associated with lower disease activity and a reduction in corticosteroid use. (12th June 2018) - Batten, R.L.; Batool, S.; Kidd, C.E.; Lorenzi, A.; Vila, J.; Walker, K.; Griffiths, B.
Abstract : Background: The recently published UK guidelines for the management of SLE recommend biologic therapy for severe or refractory disease. The British Isles Lupus Assessment Group Biologics Register (BILAG-BR) has shown rituximab (RTX) to be safe, effective and corticosteroid [CS] sparing when used to treat refractory SLE. In 2013 NHS England published an interim clinical commissioning policy statement with criteria determining when RTX can be used to treat SLE. Objectives: We evaluated our centre's RTX retreatment strategy in patients with SLE and the consequent outcomes (disease activity and CS dose). Methods: Records for the first 50 patients receiving RTX for refractory SLE who consented to join BILAG-BR from our centre between December 2013 and January 2016 were analysed (data cut off July 2016). Demographics, disease activity BILAG 2004/ SLEDAI-2K), change in CS dose, retreatment schedules and adverse events were analysed. Results: Median(IQR) age and disease duration were 42.8 (33–53) years and 9.5 (4–15.8) years respectively. Male: female ratio was 1:25. 80% were Caucasian, 6% Asian, 4% Caribbean and 10% other. All patients met SLICC/ACR classification criteria for SLE. The median(IQR) SLEDAI-2K scores and BILAG 2004 scores reduced from 6 (4–8) to 4 (0–4) (p<0.00001) and 20 (10–24.5) to 9 (2–15.5) (p<0.001) respectively at 6 months. Complete response was achieved in 62.8% patients (defined as loss of all BILAG A and B scores to ≤1B score with no new A/B scores in other organ domains). 66% patients lost all A scores at 6 months. Median(IQR) daily CS dose reduced from 10 mg(0–20) to 5 mg(0.5–9.5) at 6 months (P=<0.001) and was 5 mg (0–6.63) at last reported visit (median (IQR) 13 (12–19.5) months). 16 patients did not fully respond to baseline treatment but 11 responded to retreatment. Serious infections (requiring hospital admission) occurred in 6 patients (12%). 30/50 patients received their 1 st course of RTX at BILAG-BR baseline visit. 23 met criteria for active disease (at least 1A or 2Bs), 6 were taking an unacceptably high maintenance CS dose, and 1 was planning pregnancy. Median(IQR) CS dose in this group at baseline was 10 mg(1.5–20), and 5 mg(3–9) at 6 months. 70.8% demonstrated complete response at 6 months. 17 (57%) went on to have retreatment due to active disease, of which 11 (64.7%) had responded at 6 months post retreatment. Median(IQR) time to retreatment was 8 (6–12) months. 20/50 patients had received retreatment at predetermined intervals prior to their baseline BILAG-BR visit. Median(IQR) numbers of previous RTX courses were 3 (2–6). Median(IQR) CS dose was 8.75 mg(0–11.3) at baseline BILAG-BR visit and 5.5 mg(0–10) at 6 months. Median(IQR) time from baseline to retreatment was 6 (6–9.5) months. Median(IQR) sustained response was 18 (13.5–18) months. Conclusions: Historically, our centre used time from 1 st treatment to flare as a guide to a patient's future RTX retreatment schedule; patients were, on average, treated 2 months earlier than those treated under the current commissioning policy. Findings suggest that earlier retreatment led to sustained disease control and reduction of CS dose with no increase in adverse events. 11/16 incomplete responders responded following retreatment. Early retreatment may be associated with better outcomes for the patient and further research is needed in this area. Disclosure of Interest: None declared